2020
DOI: 10.21315/tlsr2020.31.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Analysis of Selected Macroalgal Species from the Persian Gulf as a Nutritional Resource

Abstract: Highlights • S. boveanum and S. trinodis, Phaeophyta algal species, showed the highest value of ash and polyunsaturated fatty acids contents. • Chlorophyta species "C. racemose, C. sertularioides and B. corticolans" showed the highest level of lipid and protein contents • G. rugosa and P. perforata as a Rhodophyta species showed the highest essential amino acid contents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
5
10
0
Order By: Relevance
“…Pirian et al . (2020) also reported that the lipid content of eight macroalgae species, S. boveanum , S. trinodis , H. caroides , P. perforata , G. rugosa , C. racemosa , C. sertularioides and B. corticulans from the Persian Gulf was about 1.27–9.13%. Similar to our results, Gosch et al .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Pirian et al . (2020) also reported that the lipid content of eight macroalgae species, S. boveanum , S. trinodis , H. caroides , P. perforata , G. rugosa , C. racemosa , C. sertularioides and B. corticulans from the Persian Gulf was about 1.27–9.13%. Similar to our results, Gosch et al .…”
Section: Resultsmentioning
confidence: 94%
“…temperature, humidity, location and sampling period), water resource and the presence of nutrients can affect total lipid and fatty acid content in algal biomass (Pereira et al ., 2012; Abomohra et al ., 2018). Although seaweed distribution on the coastline of the Persian Gulf in the south of Iran and their nutritional compounds, such as proteins, carbohydrates, minerals, dietary fibres, vitamins and polyunsaturated fatty acids (PUFAs) (Rohani-Ghadikolaei et al ., 2012; Pirian et al ., 2017, 2020), have already been studied, macroalgal exploitation as a source of biodiesel has not yet been fully addressed, and biodiesel indices of seaweeds from the Persian Gulf have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…fasciata has been reported to produce a novel sphingosine derivative with antiviral activity (Parsaeimehr and Chen, 2013). Seaweeds exhibit a different type and level of fatty acids and many of which possess potential bioactivity (Pirian et al, 2017;Pirian et al, 2020). Several cytotoxic compounds such as fucoidans, laminarians, and terpenoids recognized by anticancer, antitumor and antiproliferative properties are reported to be abundant in seaweeds (Selim, 2012).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The biochemical compounds isolated from algae use making antibacterial drugs. There are several native commercial seaweeds with potential of cultivation, nutritional value, and bioactive properties in tropical waters of the Persian Gulf in the southern coastlines of Iran (Pirian et al, 2017;Pirian et al, 2020;Soleimani et al, 2018;Zarei Jeliani et al, 2017a;Zarei Jeliani et al, 2017b). Although, introducing of seaweeds as available and renewable resource in this region are not completely known yet (Zarei Jeliani et al, 2017a;Zarei Jeliani et al, 2017b).…”
mentioning
confidence: 99%
“…Similar to ascidians, seaweeds are considered an important source of n -3 long-chain PUFA, especially α-linolenic acid (ALA; 18:3 n -3) and EPA [ 4 , 44 ], with their potential as ingredients for aquafeed formulations also being increasingly acknowledged [ 45 ]. Although the lipid content in seaweed is relatively low (1.27% to 9.13%) [ 46 ], these organisms feature high n -3/ n -6 ratios, making them an appealing source of a valuable source of essential FA in health-promoting diets [ 47 ].…”
Section: Introductionmentioning
confidence: 99%